Association Between Advanced Keratoconus and Serum Levels of Zinc, Calcium, Magnesium, Iron, Copper, and Selenium. Issue 10 (October 2018) - Bamdad, Shahram; Owji, Naser; Bolkheir, Alireza
Abstract : Purpose: To investigate the possibility of an association between serum levels of zinc (Zn), calcium (Ca), magnesium (Mg), iron (Fe), copper (Cu), and selenium (Se) and advanced keratoconus (KCN). Methods: In this study, 50 patients with advanced KCN and 50 control subjects were included. Plasma levels of Zn, Ca, Mg, Fe, Cu, and Se were compared between the groups. Results: Mean ± SD age of the patients in the case and control groups was 29.3 ± 3.5 and 28.9 ± 5.9 years, respectively ( P = 0.669). Among serum parameters, there were no statistically significant differences between the 2 groups in serum levels of Ca, Mg, and Fe ( P > 0.05), whereas serum levels of Zn and Cu were significantly lower in the case group than the control group [65.92 ± 7.90 vs. 87.36 ± 13.64 μg/dL and 78.48 ± 11.96 vs. 116.34 ± 20.87 μg/dL, respectively (both P < 0.001)] as well as the serum level of Se [79.76 ± 19.16 vs. 87.41 ± 15.91 μg/dL ( P = 0.032)]. Conclusions: The lower serum levels of Zn, Cu, and Se in patients with advanced KCN compared with healthy controls indicate the possible role of antioxidants in the etiopathogenesis of KCN, which points to early treatment of this progressive degenerative disease with supplementation therapy, rather than keratoplasty techniques.